Perancangan Perangkat Penampil Informasi Elektronik Otomatis Jarak Jauh - Hasanah, Sefrikha Uswatun; Pramana, Rozeff; Nugraha, Sapta (Jurnal Sustainable: Jurnal Hasil Penelitian dan Industri Terapan, 2017)
Interface information still use the bulletin board to manual. Information should be printed in advance and attached to the bulletin board to be informed. This resulted in a the delay in the delivery of information because it is manual. In this study, will be designed based automated electronic information system Raspberry Pi. Information will be sent using the telecommunications network are displayed alternately in the form of a slideshow. The results show that the system created the device can display information using the Raspberry Pi. The information is displayed in the form of pictures and a slideshow format on the monitor remotely.